BIM-based task-level planning for robotic brick assembly through image-based 3D modeling. (January 2020) - Ding, Lieyun; Jiang, Weiguang; Zhou, Ying; Zhou, Cheng; Liu, Sheng
Abstract: The application of robotics in the assembly of building bricks has become a popular topic, while the planning of construction robots is still lagged far behind the manufacturing industry. New robotic assembly task with manual teaching–planning method is always time consuming. A task-level planning method was proposed, and the implementation details were described to improve the planning efficiency of robotic brick assembly without affecting accuracy. In this work, a BIM (Building Information Model)-based robotic assembly model that contains all the required information for planning was proposed. Image-based 3D modeling was utilized to help the calibration of the robotic assembly scene and building task models. The placement point coordinates of each assembly brick were generated in the robot base coordinate system. Finally, three different building information model tasks of modular structures (e.g., wall, stair, and pyramid) were designed. The feasibility and effectiveness of the proposed method were verified by comparing the efficiency and accuracy of three models through manual teaching and task-level planning.